Herstellung von LATP für den Einsatz als Festkörperelektrolyt und dessen Eigenschaften - Hupfer, Thomas (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie - 2192-9963, 2017)
In this work, the oxide material Li???Al?Ti???(PO?)? (LATP) is extensively investigated with the scope of using it as a solid state electrolyte. Starting with the synthesis of raw LATP material by sol-gel process, the whole production process of LATP is analyzed, including powder conditioning and sintering of ceramic samples.